Water erosion and surface runoff as a function of types and rates of crop residue in two modes of direct seeding - Amaral, André Julio do; Cogo, Neroli Pedro; Bertol, Ildegardis; Santos, Pablo Grahl dos; Werner, Romeu de Souza (Revista de Ciências Agroveterinárias, 2013)
The physical conditions of the soil surface play an important role in controlling the soil water erosion and its associated surface runoff. Based on that, this study was developed with the objective of quantifying the soil and water losses by rainfall erosion, in the rates of all, half, and a quarter of the total produced of the black oat and corn residues, in the modes of direct seeding with and without shank soil-openers in the seeding-fertilizing machine. For this, was applied simulated rainfall of 75 mm h-1, with 1.5 h duration, in a Hapludox soil with 0.16 m m-1 average slope steepness. Had been evaluated some physical characteristics of the soil and the usual water erosion variables. In general, it was seen that the direct seeding with shanks increased the infiltration and the surface retention of the rainfall water in the soil and the surface retention of the eroded sediments, diminishing the runoff and the erosion. The total water loss was greater under the black oat than the corn residue, and higher in the no-tillage than furrow openers roll, this later occurrence in both types of residue and in any of their rates, but, in general, tending to increase with the increase of the latter. The total soil loss was relatively small and differed little among the modes of seeding and the rates of residue when this was that of black oat; with the corn residue, except in one case where it was great only in the direct seeding with no tillage, but expressively diminished with the increase in residue rates.